Leverage. Season 1 [videorecording (DVD)]. - Hutton, Timothy, 1960-; Hodge, Aldis; Bellman, Gina, 1966-; Kane, Christian, 1974-; Riesgraf, Beth (Paramount Home Entertainment, 2009)
Leverage follows a team of expert thieves that take down corrupt corporations in elaborate high-tech schemes. Insurance investigator Nate Ford exposed scams and recovered stolen items worth millions. But his life hit the skids when his insurance company allowed his ailing 8-year-old son to die. Years later, Nate gets even as the leader of a specialized team of thieves, computer experts and con artists that right corporate and governmental injustices against honest citizens. To expose corruption, Nate will do wrong for all the right reasons-- he will provide leverage.